Identifikasi Metode Pembelajaran dalam Rangka Mengembangkan Kemandirian Anak Usia 5-6 Tahun di Kecamatan Pringgabaya Kabupaten Lombok Timur Tahun Pelajaran 2020/2021 - Dian Helvayana; Nurhasanah Nurhasanah; Ika Rachmayani; Fahruddin Fahruddin (Indonesian Publication Center, 2021)
The purpose of this study was to identify the learning methods used by teachers in developing the independence of children aged 5-6 years in Pringgabaya District, East Lombok Regency, for the 2020/2021 academic year. This type of research is survey research. The sampling technique in this study was random sampling, with data collection methods, namely interviews and questionnaires. Questionnaires were distributed to 30 teachers who teach children aged 5-6 years (group B) in Pringgabaya District, East Lombok Regency. The data analysis used in this research is descriptive quantitative with the percentage formula. The results of the acquisition of the percentage of research identification of learning methods in developing children's independence are as follows: The method of giving the task gets the percentage of 94%, the question and answer method 93%, the project method 92%, the playing method 90%, the singing method 83%, the storytelling method 73%, the field trip method obtained a percentage of 70%. Based on the percentage results that have been obtained, it can be concluded that each learning method has a good influence in developing children's independence seen from the results of a fairly high percentage, but the majority of group B teachers in Pringgabaya District, East Lombok Regency, for the 2020/2021 academic year, tend to use this method. giving assignments as for the types of activities carried out by teachers in developing children's independence, namely free drawing, meronce, stamping techniques, collages, knowing geometric shapes, printing, with the highest percentage acquisition of 94%.